Cervical Cancer Screening and Prevention in 78 Sexually Transmitted Disease Clinics—United States, 2014–2015. Issue 10 (October 2017) - McGinnis, Emily; Meyerson, Beth E.; Meites, Elissa; Saraiya, Mona; Griesse, Rebecca; Snoek, Emily; Haderxhanaj, Laura; Markowitz, Lauri E.; Smith, William
Abstract : Background: Human papillomavirus (HPV) infections cause approximately 30, 700 cancers annually among US men and women, cervical cancer being the most common. Human papillomavirus vaccination is recommended routinely for US girls and boys at age 11 to 12 years, and for those not previously vaccinated, through age 26 and 21 years for women and men, respectively. Our objective was to assess current cervical cancer screening and HPV vaccination practices among sexually transmitted disease (STD) clinics in the United States. Methods: We surveyed a geographically diverse convenience sample of US STD clinics identified by members of the National Coalition of STD Directors within 65 state, territorial, and local jurisdictions. An online multiple-choice survey about clinical services was administered to clinic directors or designees during October 2014 to February 2015. Results: Survey respondents included 78 clinics from 46 states and territories. Of these clinics, 31 (39.7%) offered both cervical cancer screening and HPV vaccination, 6 (7.7%) offered cervical cancer screening only, 21 (26.9%) offered HPV vaccination only, and 20 (25.6%) offered neither cervical cancer prevention service. Among those not offering the service, the most commonly reported barrier to cervical cancer screening was time constraints (25/41, 61.0%); for HPV vaccination it was reimbursement (11/26, 42.3%). Conclusions: By early 2015, in a geographically diverse group of 78 STD clinics, 39.7% provided nationally recommended HPV vaccination and cervical cancer screening, whereas 25.6% provided neither. Further research could identify strategies for STD clinics to reduce HPV-associated cancers by increasing provision of HPV vaccination and cervical cancer screening services, particularly among medically underserved populations. Abstract : An assessment of cervical cancer prevention services at 78 US sexually transmitted disease clinics found that less than 40% offered both human papillomavirus vaccination and cervical cancer screening, suggesting room for improvement.